2015
DOI: 10.1002/oby.21327
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water and non‐nutritive sweetened beverages on weight loss and weight maintenance: A randomized clinical trial

Abstract: ObjectiveTo evaluate the effects of water versus beverages sweetened with non‐nutritive sweeteners (NNS) on body weight in subjects enrolled in a year‐long behavioral weight loss treatment program.MethodsThe study used a randomized equivalence design with NNS or water beverages as the main factor in a trial among 303 weight‐stable people with overweight and obesity. All participants participated in a weight loss program plus assignment to consume 24 ounces (710 ml) of water or NNS beverages daily for 1 year.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 31 publications
5
113
0
14
Order By: Relevance
“…13 Several studies involving more than 100 000 new participants and representing several new geographic settings have since been published. [14][15][16][17][18][19][20][21][22][23][24] Our objective was to synthesize evidence addressing this question: Is routine consumption of nonnutritive sweeteners by adults and adolescents associated with adverse long-term cardiometabolic effects in RCTs and prospective cohort studies?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Several studies involving more than 100 000 new participants and representing several new geographic settings have since been published. [14][15][16][17][18][19][20][21][22][23][24] Our objective was to synthesize evidence addressing this question: Is routine consumption of nonnutritive sweeteners by adults and adolescents associated with adverse long-term cardiometabolic effects in RCTs and prospective cohort studies?…”
Section: Discussionmentioning
confidence: 99%
“…Weight Among 5 RCTs evaluating interventions using nonnutritive sweeteners in participants who were obese, 19,20,34,35,38 there was no consistent effect on change in weight (standardized MD -0.17; 95% CI -0.54 to 0.21; I 2 81%; 5 trials; 791 participants) ( Table 3, Figure 2C). Heterogeneity across the 5 trials was partially explained by differences in study duration: 2 longer trials 19,38 showed significant weight loss over 16 to 24 months of the intervention (standardized MD -0.55, 95% CI -0.75 to -0.34; I 2 0%; 2 trials), and 3 shorter (6 mo) trials 20,34,35 showed no effect for the use of nonnutritive sweeteners (standardized MD 0.13, 95% CI -0.34 to 0.59; I 2 65%; 3 trials) (p for subgroup differences = 0.009; Appendix 1, Table S6).…”
Section: Secondary Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…En este sentido, es importante no perder de vista el impacto de la incorporación de bebidas y alimentos que contienen edulcorantes no nutritivos (NNS) en la calidad de la dieta evaluando beneficios y riesgos (34) para la salud (35). A pesar de que las intervenciones a corto plazo sugieren que el uso de NNS puede ser útil para apoyar la reducción de la ingesta energética y para promover el control glucémico y del peso (35,36), se ha creado una gran controversia, especialmente en cortes longitudinales que correlacionaron su consumo con la obesidad o con la DM2 (37 ción controvertida de mecanismos periféricos y centrales, tras el argumento de que estos no son compuestos fisiológicamen-te inertes, con potencial acción sobre el equilibrio energético influyendo en receptores orales y extraorales del sabor dulce y efectos sobre la secreción hormonal, así como la posible inducción a la conducta adictiva a través de los receptores opioides (38). Sin embargo, se requieren más estudios directos de este tipo sobre la estevia, específicamente en humanos.…”
Section: Discussionunclassified